INDUSTRI KUE TRADISIONAL KHAS MELAYU DI KAWASAN SEBERANG KOTA JAMBI 1984 – 2016 - Isnawati, Siti Heidi Karmela (Universitas Batanghari Jambi, 2019)
AbstractThis research is a historical research with the theme of economic history with the main problem is the development of the traditional Malay cake industry that is traditionally inhabited by Jambi residents in the Seberang Region of Jambi City from 1984 to 2016. The purpose of this thesis is to explain the emergence and development of the traditional cake industry in Seberang area of Jambi City which eventually became the center of traditional Malay cake production. Another goal is to describe the contribution, role, and influence of the traditional pastry culinary industry on the economic life of the population and other local economic sectors in the Seberang Region of Jambi City. Some theories used are Schumpeter's theory of the role of entrepreneurs who are also innovators in creating economic growth. For the research method is the historical method, through several stages, namely heuristics (the personal archive of cake makers, interviews, and other written sources), criticism, interpretation and writing. The findings in the field show that the business of making traditional cakes in the Seberang area of Jambi City has been developing from time to time although it is still on a home industry scale, this is indicated by the continued increase in the number of traditional cake makers in Danau Teluk and Pelayangan Districts, as well as the expanding marketing area. traditional cake products to the regional level. In addition it is known that this type of traditional pastry business is in the form of a private business and there is also a joint / group business.Keywords: Home Industry, Traditional Cakes, Across the City of Jambi AbstrakPenelitian ini merupakan penelitian sejarah yang bertemakan sejarah ekonomi dengan permasalahan pokoknya adalah perkembangan industri kue tradisional khas Melayu Jambi yang ditekuni penduduk di Kawasan Seberang Kota Jambi sejak tahun 1984 hingga tahun 2016. Adapun Tujuan dari penulisan skripsi ini untuk menjelaskan kemunculan dan perkembangan industri kue tradisional di Kawasan Seberang Kota Jambi yang pada akhirnya menjadi sentra produksi kue tradisional khas Melayu Jambi. Tujuan lainnya yaitu menggambarkan kontribusi, peranan, dan pengaruh industri kuliner kue tradisional terhadap kehidupan ekonomi penduduk dan sektor ekonomi lokal lainnya di Kawasan Seberang Kota Jambi. Beberapa teori yang digunakan adalah teori Schumpeter tentang peranan pengusaha yang juga menjadi innovator di dalam menciptakan pertumbuhan ekonomi. Untuk metode penelitiannya adalah metode sejarah, melalui beberapa tahapan yaitu heuristik (arsip pribadi pembuat kue, wawancara, dan sumber tertulis lainnya), kritik, interpretasi dan penulisan. Hasil temuan di lapangan menunjukkan bahwa usaha pembuatan kue tradisional di Kawasan Seberang Kota Jambi mengalami perkembangan dari waktu ke waktu meskipun masih berskala industri rumah tangga, hal ini ditandai dengan terus bertambahnya jumlah pembuat kue tradisional di Kecamatan Danau Teluk dan Pelayangan, serta makin luasnya daerah pemasarann produk kue tradisional hingga ke tingkat regional. Selain itu diketahui bahwa jenis usaha kue tradisional ini ada yang berbentuk usaha pribadi dan ada juga yang berbentuk usaha bersama/kelompok.Kata Kunci: Industri Rumah Tangga, Kue Tradisional, Seberang Kota Jambi